Kajian Pemanfaatan Eceng Gondok (Eichornia crassipes) Sebagai Pakan Ternak Itik Alabio (Anas platyrhynchos Borneo) - Siska Fitriyanti (Pusbindiklat - LIPI, 2019)
An efficient feeding strategy is utilizing abundant and nutritious local resources for livestock. Fermented hyacinths can be used as a substitute feed for ducks, which are widely available in natureand still not well utilized. On the other hand, water hyacinth also has a fairly good nutritional content to serve as a ducks feed intake. The purpose of this study is to determine the effect of feed consisting of water hyacinth fermentation to the growth of Alabio ducks. The results obtained were feed with 75% concentration of fermented hyacinths giving the best result for Alabio duck growth when compared with duck given commercial feed.